How Camera-to-Subject Distance and Height Affect Breast Measurement and Follow-Up Assessment in Plastic Surgery - Xie, Jiangmiao; Zhang, Wenchao; Yang, Elan; Yu, Nanze; Xia, Zenan; Liu, Xiaoli; Xie, Yaning; Chen, Sichao; Zeng, Ang (Aesthetic plastic surgery, 2024)
Background Due to several factors that affect photograph quality, bias is inevitably present in two-dimensional (2D) breast photography. The principal variables affecting image performance at a fixed focus length are the distance between the camera and the subjects and the photography angles. Objective This study aimed to investigate the effects of camera-to-subject distances and camera height on breast measurement parameters to understand the trend of breast deformation and provide guidance for the accurate evaluation of planar follow-up. Methods We enlisted 16 volunteers with various breast cup sizes (A–D). Frontal and lateral photos were obtained with a steady focus of 50 mm at distances between 1.10 m and 2.20 m and at heights between 30 cm above the nipple and 30 cm below the nipple at intervals of 10 cm. Two researchers independently evaluated each volunteer’s breast aesthetic parameters, including 11 linear parameters, 3 area parameters, and 3 ratio parameters, using Vernier calipers and Photoshop. Results The correlation coefficient of the two investigators ranged from 0.922 to 0.999. The results measured by Photoshop were 29.67 ± 5.23% greater than those of the Vernier caliper ( p < 0.01). In contrast to ratio parameters, which showed no significant changes in each distance group ( p = 1.00), linear parameters and area parameters significantly increased as object distance decreased ( p < 0.05). The lower pole of the breast grew wider and flatter and occupied a larger proportion of the breast as height declined. Conclusion Camera-to-subject distances of 1.5–1.7 m are recommended for stabilized and uniform breast photography. Varying shooting height affects breast distortion. Quantifying the relationship between photographic conditions and breast morphology enables plastic surgeons to conduct more comprehensive and accurate assessments. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266. Bullet point list: The breast morphology will get more distortion with a smaller camera-to-subject distance. Camera-to-subject distances of 1.5~1.7m are recommended for stabilized and uniform breast photography. Height rather than distance affects the breast proportion.